Addiction and virtue: beyond the models of disease and choice - Dunnington, Kent (Strategic initiatives in evangelical theology, 2011)
What is the nature of addiction? Neither of the two dominant models (disease or choice) adequately accounts for the experience of those who are addicted or of those who are seeking to help them. In this interdisciplinary work, Kent Dunnington brings the neglected resources of philosophical and theological analysis to bear on the problem of addiction. Drawing on the insights of Aristotle and Thomas Aquinas, he formulates an alternative to the usual reductionistic models. Going further, Dunnington maintains that addiction is not just a problem facing individuals. Its pervasiveness sheds prophetic light on our cultural moment. Moving beyond issues of individual treatment, this groundbreaking study also outlines significant implications for ministry within the local church context